Patterns of help‐seeking in women when problems arise in their sexual life: a discussion paper. Issue 23 (13th September 2013) - Azar, Mathilde; Bradbury‐Jones, Caroline; Kroll, Thilo
Abstract : Aims and objectives: To explore patterns of help‐seeking in women who have sexual dysfunction and the implications for nursing practice. Background: Female sexual dysfunction is a common problem that is under‐reported and untreated. Barriers to help‐seeking reported in existing literature relate to the perception among many women that sexual dysfunction is: part of the normal ageing process; not bothersome or does not exist; an issue that health professionals are reluctant to address; a taboo subject. However, little is known about patterns of help‐seeking in women with sexual problems. This leaves a potential gap in nursing knowledge regarding appropriate, supportive strategies. Design: Discursive inquiry framed theoretically by Vogel's model. Methods: A literature review was undertaken by searching relevant databases. A combination of keywords was used to identify peer‐review papers relating to women's help‐seeking behaviour for sexual dysfunction. Vogel's model was used as a framework to extract relevant information from the papers and structure the discussion. Results: Vogel's model comprises four steps: encoding and interpreting, generating options, decision‐making and evaluation of behaviour. Using this stepwise approach helped elucidate the complex mechanisms associated with help‐seeking in a structured manner. The key issues associated with help‐seeking intention are concerned with women's personal awareness of and interaction with the environment. Conclusions: Vogel's model offers a new approach to understanding the dynamics that underpin women's decisions to seek professional help when sexual concerns arise and also provides a useful framework for nurses to consider women's specific sexual concerns. Relevance to clinical practice: Implications for nursing practice are focused on public awareness, women's empowerment and the provision of effective sexual health care. Because sexual dysfunction is a global phenomenon, it is likely that the discussion in this paper will be relevant to an international, nursing readership.